2011
DOI: 10.1007/s00449-011-0522-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of 1,3-propanediol using raw glycerol with immobilized Clostridium beijerinckii NRRL B-593 in comparison to suspended culture

Abstract: The continuous production of 1,3-propanediol (1,3-PDO) was investigated with Clostridium beijerinckii NRRL B-593 using raw glycerol without purification obtained from a biodiesel production process. Ceramic rings and pumice stones were used for cell immobilization in a packed-bed bioreactor. For comparison purpose, a control bioreactor with suspended culture was also run. The effect of hydraulic retention time (HRT) on the production of 1,3-PDO in both immobilized and suspended bioreactors were also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 18 publications
5
29
0
6
Order By: Relevance
“…Similar concentrations (56 g l -1 ) were reported by Hiremath et al who used glycerol obtained from Jatropha seed biodiesel production (Hiremath et al, 2011). C. beijerinckii was also reported to produce 1,3-PDO from raw glycerol (Gungormusler et al, 2011). Notably, productivity was increased to 1.51 g l -1 h -1 when using raw glycerol as compared to 0.84 g l -1 h -1 when using pure glycerol .…”
Section: Raw Glycerolsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar concentrations (56 g l -1 ) were reported by Hiremath et al who used glycerol obtained from Jatropha seed biodiesel production (Hiremath et al, 2011). C. beijerinckii was also reported to produce 1,3-PDO from raw glycerol (Gungormusler et al, 2011). Notably, productivity was increased to 1.51 g l -1 h -1 when using raw glycerol as compared to 0.84 g l -1 h -1 when using pure glycerol .…”
Section: Raw Glycerolsupporting
confidence: 80%
“…Gungormusler et al reported 1,3-PDO production from raw glycerol with use Clostridium beijerinckii cells immobilized to ceramic rings and pumice stones in combination with a hydraulic retention time system. They could show an increase in productivity and yield for 1,3-PDO production and predicted a maximal 1,3-PDO production rate of 30 g l -1 h -1 (Gungormusler et al, 2011).…”
Section: Biotechnological Production Of 13-pdomentioning
confidence: 99%
“…Benefits conferred by cell immobilization might include increased stability in unfavorable environmental conditions during operation as well as avoiding washout [33,131,132]. For example, with microencapsulation, the biomass of K. pneumoniae was increased 2.6-fold compared to free cell cultures [33].…”
Section: Fermentationmentioning
confidence: 99%
“…It was observed that cell immobilization had better robustness and reliability compared to suspended cells. Production in packed bed bioreactor designed with immobilization system achieved 2.5-fold higher productivity compared to free system, which had advantageous properties over free cell system (Gungormusler et al 2011). The production of lactose with β-D-galactosidase in a packed bed bioreactor was studied with immobilized yeast cells in calcium alginate gel (Panesar et al 2010).…”
Section: Packed Bed Reactorsmentioning
confidence: 98%